The New Industrial State - Galbraith, John Kenneth 1908-2006 (The James Madison Library in American Politics, 2015)
With searing wit and incisive commentary, John Kenneth Galbraith redefined America's perception of itself in The New Industrial State, one of his landmark works. The United States is no longer a free-enterprise society, Galbraith argues, but a structured state controlled by the largest companies. Advertising is the means by which these companies manage demand and create consumer "need" where none previously existed. Multinational corporations are the continuation of this power system on an international level. The goal of these companies is not the betterment of society, but immortality through an uninterrupted stream of earnings. First published in 1967, The New Industrial State continues to resonate today